2014
DOI: 10.1038/srep04990
|View full text |Cite
|
Sign up to set email alerts
|

Powerful inner/outer controlled multi-target magnetic nanoparticle drug carrier prepared by liquid photo-immobilization

Abstract: Nanomagnetic materials offer exciting avenues for advancing cancer therapies. Most researches have focused on efficient delivery of drugs in the body by incorporating various drug molecules onto the surface of nanomagnetic particles. The challenge is how to synthesize low toxic nanocarriers with multi-target drug loading. The cancer cell death mechanisms associated with those nanocarriers remain unclear either. Following the cell biology mechanisms, we develop a liquid photo-immobilization approach to attach d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…To address this, Chen et al 17 developed a magnetic drug-delivery system in which doxorubicin (DOX) was chemically bonded to Fe 3 O 4 NPs, and it was then embedded in polyethylene glycol (PEG) to functionalize the porous silica shell. Similarly, Guan et al 18 developed a multitargeted oleic acid (OA)–MNPs and demonstrated an excellent in vivo and in vitro efficacy in treating the human cervical cancer HeLa cells. These studies concluded that MNPs loaded with effective antitumor drugs offered physical therapy, which has advantages over the other nonloaded drugs, such as small particle size, large specific surface, high-capacity coupling, and good magnetic response.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, Chen et al 17 developed a magnetic drug-delivery system in which doxorubicin (DOX) was chemically bonded to Fe 3 O 4 NPs, and it was then embedded in polyethylene glycol (PEG) to functionalize the porous silica shell. Similarly, Guan et al 18 developed a multitargeted oleic acid (OA)–MNPs and demonstrated an excellent in vivo and in vitro efficacy in treating the human cervical cancer HeLa cells. These studies concluded that MNPs loaded with effective antitumor drugs offered physical therapy, which has advantages over the other nonloaded drugs, such as small particle size, large specific surface, high-capacity coupling, and good magnetic response.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were prepared using the liquid photo-immobilization method 30. First, we examined the chemical bonding between the functional groups of the drug molecules and NPs upon photo-immobilization using Fourier transform infrared spectroscopy (FTIR).…”
Section: Resultsmentioning
confidence: 99%
“…The photoactive NGF (abbreviated AzPhNGF) was synthesized in our laboratory following the procedure presented in Figure 1 of Ref 30. All treatments were conducted in dark room.…”
Section: Methodsmentioning
confidence: 99%
“…The polymeric shell provides biocompatibility, prevents agglomeration, and acts as a drug reservoir. Several polymers such as starch, dextran [54,55], PEG [51,56], fatty acids, polyvinyl alcohol [57], polyacrylic acid, poly lactides, gelatin, silica [58,59,56], oleic acid [60,61], PLGA or poly(D,L-lacticco-glycolic acid) [62], polyethylene imine (PEI) [63], poly methyl methacrylate (PMMA), and polyacrylic acid (PAA) [59,64], albumin [50,41], and chitosan [64] have been used as coating materials for different purposes. Conjugation of outer shell with different targeting molecules can promote sitespecific function of magnetic NPs.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%